Synergy of Law and Education in the Protection of Contract Workers in Indonesia - Arifuddin Muda Harahap; Safinatul Hasanah Harahap; Zulpahmi Lubis (Jurnal Cendikia ISNU SU, 2024)
This study discusses the synergy between law and education in providing protection for contract workers in Indonesia. Contract workers are one of the labor groups that often face problems related to legal status, job uncertainty, and limitations in obtaining normative rights as stipulated in labor regulations. Although Law Number 13 of 2003 on Manpower and its derivative regulations have provided a legal framework, implementation in the field often shows that there are loopholes that weaken the position of contract workers. Therefore, an interdisciplinary approach is needed that integrates the legal and educational dimensions to provide more comprehensive protection. The research method used is normative legal research with a qualitative approach, through an examination of laws and regulations, doctrines, and labor practices, and enriched with educational studies that emphasize the importance of legal literacy for workers. The results of the study show that legal protection for contract workers has not been fully effective due to weak supervision, low understanding of workers about their rights, and the practice of contract abuse by employers. In this context, education plays an important role as an important instrument to increase the legal awareness of contract workers, both through formal and non-formal education, as well as legal and employment skills-based training. The conclusion of this study confirms that legal and educational synergy is a relevant strategy to strengthen the protection of contract workers. The law provides a binding normative framework, while education forms the awareness and empowerment of workers in demanding their rights. Thus, the combination of the two is expected to be able to realize social justice and improve the welfare of contract workers in Indonesia.